Interleaved silent steady state (ISSS) imaging: A new sparse imaging method applied to auditory fMRI - Schwarzbauer, Christian; Davis, Matt H.; Rodd, Jennifer M.; Johnsrude, Ingrid (NeuroImage (Orlando, Fla.), 2006)
The acoustic scanner noise that is generated by rapid gradient switching in echo planar imaging (EPI) is an important confounding factor in auditory fMRI. “Sparse imaging” designs overcome the influence of scanner noise on stimulus presentation by acquiring single brain volumes following a silent stimulus presentation period. However, conventional sparse imaging requires assumptions about the time-to-peak of the evoked hemodynamic response and reduces the amount of EPI data which can be acquired and hence statistical power. In this article, we describe an “interleaved silent steady state” (ISSS) sampling scheme in which we rapidly acquire a set of EPI volumes following each silent stimulus presentation period. We avoid T 1-related signal decay during the acquisition of the EPI volumes by maintaining the steady state longitudinal magnetization with a train of silent slice-selective excitation pulses during the silent period, ensuring that signal contrast is constant across successive scans. A validation study comparing ISSS to conventional sparse imaging demonstrates that ISSS imaging provides time course information that is absent in conventional sparse imaging data. The ISSS sequence has a temporal resolution like event-related (ER) imaging within a single trial (unlike conventional sparse imaging, where ER-like temporal resolution can only be achieved by compiling data across many jittered trials of the same stimulus type). This temporal resolution within trials makes ISSS particularly suitable for experiments in which a) scanner noise would interfere with the perception and processing of the stimulus; b) stimuli are several seconds in duration, and activation is expected to evolve and change as the stimulus unfolds; and c) it is impractical to present a single stimulus more than once (for example, repetition priming or familiarity effects would be expected).